(untitled) (The Peerian Journal, 2024)
Babylon Hotel is one of the most important areas with high potential and the ability to attract tourists in Iraq, and business relations require needs to attract tourists and develop them in such excellent hotels, and one of the most important needs that the hotel sector cares about is information technology through new communication tools, and tourism marketing through information and communications technology and creating an information environment for each tourism institution plays a major role in obtaining job opportunities in the tourism market, and on the other hand, the presence of information banks for tourism awareness in identifying and providing effective tools and facilities in determining the demand for hotels, and social media is a social need and has the ability to shape such important tourism practices, and what this article discusses is a descriptive case study to collect field information from those in charge of tourism marketing and information technology, and questionnaires were adopted from two groups of executive managers of Babylon Tourist Hotel, which include (hotel management, human resources manager, hotel sales and marketing specialists) and tourists and guests who visit this hotel, and SPSS and LISREL programs were used to prove the research hypotheses. The research results concluded that awareness of information technology and the effectiveness of the digital brand, online marketing and mobile marketing have a major role in increasing hotel demand.